2023
DOI: 10.1007/s00167-023-07394-z
|View full text |Cite
|
Sign up to set email alerts
|

The coronal plane alignment of the knee classification does not correlate with the functional knee phenotype classification

Abstract: Purpose It is now well established that the coronal anatomy of the lower limb is highly variable both in non-arthritic subjects and subjects undergoing total knee arthroplasty (TKA). Two new classiications were recently described independently, but never compared: functional knee phenotypes classiication and coronal plane alignment of the knee (CPAK) classiication. The hypothesis of this study was that there was a signiicant diference between the values of the hip-knee-ankle angle (HKA) and the arithmetic hip-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…The mHKA takes into account the angle between femoral and tibial mechanical axis, whereas the aHKA focuses more on the difference between femoral and tibial joint lines. Thus, functional knee phenotypes and CPAK, although both focus on coronal lower limb alignment, are two different classifications [14]. However, the deviation between aHKA and mHKA became greater along with a more VAR alignment (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mHKA takes into account the angle between femoral and tibial mechanical axis, whereas the aHKA focuses more on the difference between femoral and tibial joint lines. Thus, functional knee phenotypes and CPAK, although both focus on coronal lower limb alignment, are two different classifications [14]. However, the deviation between aHKA and mHKA became greater along with a more VAR alignment (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The results of three radiographic studies [13, 19, 27] based on a total of 11,598 Caucasian OA knees and 200 Chinese OA knees showed that the FMA measurements were similar to the present study (Caucasian: 91.4° ± 2.9° [27] and 92.7° ± 2.8° [13] vs. Chinese: 91.3° ± 1.8° [19] and 91.3° ± 3.2°), but the TMA (Caucasian: 86.8° ± 3.1° [27] and 87.2° ± 3.2° [13] vs. Chinese: 85.7° ± 2.1° [19] and 84.7° ± 4.4°), the mHKA (Caucasian: 177.3° ± 7.6° [13] vs. Chinese: 172.5° ± 3.4° [19] and 172.1° ± 7.2°) and the aHKA (Caucasian: 179.9° ± 4.8° [13] vs. Chinese: 177.0° ± 2.6° [19] and 176.0° ± 6.2°) in Caucasian OA knees were more neutral [14]. Interestingly, studies noted that the Caucasian OA males had more VAR mHKA, FMA and TMA than the females [7, 13].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study compared the CPAK classification with the functional knee phenotype classification by applying both classifications to a total of 520 patients and comparing the values of the leg alignment parameters for each individual [18]. A fundamental difference between these classifications is that CPAK uses aHKA, and Hirschmann et al use mHKA to determine overall leg alignment.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Hirschmann et al [ 16 ] studied coronal plane alignment of normal subjects and defined different global, femoral and tibial phenotypes. Jenny et al [ 17 ] compared CPAK classification with the functional knee phenotype classification and found significant differences and a weak correlation between HKA and aHKA in the same individuals.…”
Section: Discussionmentioning
confidence: 99%